Antimicrobial alkali-activated slag through self-intercalation of benzoate in layered double hydroxides. (July 2022) - Kang, Xiaojuan; Ye, Hailong
Abstract: Antimicrobial alkali-activated slag (AAS) with biocidal effectiveness is a promising cementitious binder for concrete infrastructure threatened by microbially induced concrete corrosion (MICC). In this work, the influence of sodium benzoate on the chemical reaction, phase assemblage, microstructure, and nanostructure of AAS was studied, with a particular focus on the potential in-situ formation of benzoate-intercalated layered double hydroxides (BZ-LDHs). In addition, the lattice structure, molecular bonds, and intercalation chemistry of pure BZ-LDHs synthesised using rehydration method were investigated. The results evidence the in-situ formation of BZ-LDHs in AAS incorporating sodium benzoate during alkaline activation. The benzoate anions are spontaneously intercalated in a bilayer manner in the interlayers of LDHs, with an average basal spacing of 1.568 nm. The incorporation of BZ slightly lowers the reaction degree of slag in AAS, but barely affects the composition and structure of calcium-aluminosilicate-hydrate (C-A-S-H) formed. The developed antimicrobial AAS with BZ-LDHs demonstrates remarkable bactericidal efficacy with a 95.0% effectiveness (when admixed with 3% BZ) in suppressing the growth of sulphur-oxidising bacteria Acidithiobacillus thiooxidans in this study.